2017
DOI: 10.1021/acs.langmuir.7b00645
|View full text |Cite
|
Sign up to set email alerts
|

Concerted Electrodeposition and Alloying of Antimony on Indium Electrodes for Selective Formation of Crystalline Indium Antimonide

Abstract: The direct preparation of crystalline indium antimonide (InSb) by the electrodeposition of antimony (Sb) onto indium (In) working electrodes has been demonstrated. When Sb is electrodeposited from dilute aqueous electrolytes containing dissolved SbO, an alloying reaction is possible between Sb and In if any surface oxide films are first thoroughly removed from the electrode. The presented Raman spectra detail the interplay between the formation of crystalline InSb and the accumulation of Sb as either amorphous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…First, on a clean In electrode devoid of a native oxide, atop In atoms react readily with electrodeposited metals. Similar to what was previously observed for the controlled formation of InSb 55 and InAs 56 by electrodeposition, the results reported here indicate clear formation of a crystalline In intermetallic compound upon Pd electrodeposition. Second, the sole identifiable product in these control experiments is Pd 3 In 7 .…”
Section: Discussionsupporting
confidence: 91%
“…First, on a clean In electrode devoid of a native oxide, atop In atoms react readily with electrodeposited metals. Similar to what was previously observed for the controlled formation of InSb 55 and InAs 56 by electrodeposition, the results reported here indicate clear formation of a crystalline In intermetallic compound upon Pd electrodeposition. Second, the sole identifiable product in these control experiments is Pd 3 In 7 .…”
Section: Discussionsupporting
confidence: 91%
“…[13,14] TBs have attracted worldwide attention due to their unique chemical, electrochemical, and electronic properties, and they have found applications in photovoltaic devices, [15] sensors, [16] and NIR solar cells, [17] among others. Given that excellent TBs have low transmittance in the NIR range and high transmittance in the visible range, [18] nano-TBs were identified as potential NIR radiation shielding materials, [19] especially when compared to current benchmark materials, including lanthanum hexaboride (LaB 6 ), [20] indium or antimony doped tin oxide (In-SnO 2 , Sb-SnO 2 ), [21,22] where nano-TBs can be used as additives at low concentrations to improve the NIR shielding performance of coatings significantly. In addition, K. Adachi et al synthesized Na 0.33 WO 3 and found its significant NIR absorption effect.…”
Section: Doi: 101002/adem202301003mentioning
confidence: 99%
“…Currently, established deposition processes for growing high-quality crystalline GaAs and In x Ga 1– x As include molecular beam epitaxy (MBE), organometallic vapor-phase epitaxy (OMVPE), liquid-phase epitaxy (LPE), and other methods that require high-cost and high-energy growth setups and the use of toxic precursors, ultrahigh vacuum, and extreme temperatures during growth. Conventional electrodeposition is an alternative growth method that eliminates the necessity of high-cost experimental setups, hazardous precursors, or extreme pressures but faces other obstacles that lead to impurity contamination from the electrolyte solution and amorphous growth without subsequent annealing at temperatures above 250 °C. The growth method implemented in this research is known as the electrochemical liquid–liquid–solid (ec-LLS) process, which overcomes obstacles to crystalline growth typically faced by electrochemical methods by utilizing a liquid metal electrode of a select composition to perform the electroreduction of compounds in solution and serve as a platform for semiconductor growth . Several recent studies have shown evidence of the ec-LLS growth of crystalline semiconductor thin films achieved at ambient pressure and near-room temperature via benchtop growth setups. …”
Section: Introductionmentioning
confidence: 99%